Using of AODV Protocol to Develop Trust-Based Routing Algorithms in Wireless Sensor Networks - Mojarad, Musa; Mousavipoor, Sayed Ebrahim; Mansourkhani, Ali Kohan (International Journal of Scientific Research in Computer Science and Engineering, 2021)
Wireless sensor networks (WSNs) are the most widely used field of high-potential network generations in unpredictable and dynamic environments. However, these networks are vulnerable due to their open media, changing and dynamic topology and routing algorithms. Case networks and wireless networks support various features such as dynamic self-organization, self-configuration, self-correction, easy maintenance, high scalability and reliable services. Despite the many features mentioned, this network is very susceptible to damage caused by attacks. In this paper, an energy-aware routing algorithm for WSNs is presented that uses level-to-level clustering. This technique is used to increase the network lifetime, where the network area is divided into different levels according to the radio range of the nodes and clustering is done separately in each level. This routing method is developed based on the AODV routing protocol and uses a multi-path routing technique. The simulation was performed by MATLAB software in the presence of a DoS attack. The experimental results show that the evaluation criteria in the proposed algorithm such as throughput and network lifetime against DoS attack have improved compared to other similar algorithms.